2000
DOI: 10.1046/j.1442-200x.2000.01251.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of rotavirus infection in Thailand

Abstract: Rotavirus is a major cause of acute severe diarrhea in children worldwide and an important cause of death among young children in developing countries. Group A rotaviruses are antigenically complex and multiple serotypes infect humans. Reassortant rotavirus vaccines are now available which offer protection against severe illness caused by rotavirus serotypes G1-4. Before vaccines are introduced into target populations, it is necessary to establish the baseline data of the epidemiology of rotavirus infection in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
49
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 32 publications
9
49
1
Order By: Relevance
“…This pattern was not observed in the south, where there are only two seasons per year, the rainy and the dry seasons. Rotavirus infections occurred almost all year in the south, with less distinct seasonal differences (13,20,23,24). Our results are similar to those of studies conducted in Korea, China, and Thailand but differed from those of a Japanese study, in which rotavirus was rarely detected from September to December (9,20,29,33).…”
Section: Rotavirus Infectionsupporting
confidence: 71%
See 1 more Smart Citation
“…This pattern was not observed in the south, where there are only two seasons per year, the rainy and the dry seasons. Rotavirus infections occurred almost all year in the south, with less distinct seasonal differences (13,20,23,24). Our results are similar to those of studies conducted in Korea, China, and Thailand but differed from those of a Japanese study, in which rotavirus was rarely detected from September to December (9,20,29,33).…”
Section: Rotavirus Infectionsupporting
confidence: 71%
“…Moreover, our study indicated that there was a trend of decreasing rates of rotavirus infection in the older children. This might partly be explained by the fact that older children acquired protective immunity during previous exposures to rotavirus and are therefore more resistant to infection with this agent (13,20). In addition to the age distribution of rotavirus infection, many studies have indicated a higher ratio of infected males to infected females (8,24,26,28,30).…”
Section: Rotavirus Infectionmentioning
confidence: 99%
“…Although epidemiological surveillance and genotype identification of rotavirus infections in human and pig populations in Chiang Mai, Thailand, have been carried out extensively over the past two decades, the P[10] genotype had never been reported previously [Maneekarn and Ushijima, 2000;Maneekarn et al, 2006;Khamrin et al, 2006bKhamrin et al, , 2007cChan-It et al, 2008]. The present study conducted in 2005 described the detection of an unusual strain of G3P[10] (CMH079/05) in a 2-year-old boy admitted to hospital with acute gastroenteritis.…”
Section: Discussionmentioning
confidence: 90%
“…The studies of rotavirus infection carried out in Thailand revealed that rotaviruses are the leading etiologic pathogens that causes diarrhea in children, and are responsible for about 27-58% of diarrheal diseases in hospitalized cases [Maneekarn and Ushijima, 2000;Jiraphongsa et al, 2005;Khamrin et al, 2006b]. Epidemiological surveillance of group A rotavirus infection conducted in Chiang Mai, Thailand, during the period of 2000-2004 [Khamrin et al, 2006b[Khamrin et al, , 2007c During these extensive epidemiological studies, rotavirus strains with unusual G-P combinations were occasionally detected in children hospitalized with acute gastroenteritis; for example, an unusual strain of human rotavirus G3P[3] (CMH222) bearing simian-like VP7 and caprine-like VP4 genes was isolated from a 2-year-old child patient in 2001 [Khamrin et al, 2006a].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive epidemiological studies of rotavirus infection worldwide indicated that G1 was the most prevalent genotype (5,13,15,19,21,28,36). However, the new variants G2 and G3 emerged to become the leading genotypes in Japan from 2001 to 2004 (24,35).…”
Section: Discussionmentioning
confidence: 99%